Nursing-related skeletal muscle injuries (Research, Society and Development, 2020)
Objective: to identify the profile of skeletal muscle injuries caused during nursing work. Methodology: This is a descriptive exploratory study with a quantitative approach, conducted with 42 professionals of the nursing team of a emergency care unit in the city of Caxias-MA. Data were collected through two instruments: one with the sociodemographic characterization and the other with the Nordic Musculoskeletal Questionnaire (QNSO). Results: The main complaints of nursing professionals were pain in the dorsal and lumbar region (19%), there was an equal percentage of those who reported discomfort in the neck and shoulder (11.9%), neck and dorsal zone (11.9 %), neck and lumbar zone (11.9%), followed by shoulder (9.5%). The profile of the professionals is characterized by a high prevalence of females (81.0%), most of them nursing technicians (62.6%), showing that nursing remains a predominantly female profession and for them not. having the same muscle development potential as men are more likely to develop work-related musculoskeletal disorders (WRMS). Conclusion: The high rate of musculoskeletal disorders among workers may be the beginning of awareness for managers and employees of institutions to jointly seek solutions to reduce the occurrence of these injuries on the working conditions of these professionals.